«Turkestan treaty» as a guarantee of Kazakh-Uzbek relations. (Journal of Oriental Studies, 2016)
The article discusses the main treaty of the Kazakh-Uzbek relations. The author examines several important documents which are called «Turkestan contract» and «Treaty of Eternal Friendship».
Keywords: kazakh-uzbek relations; Central Asia; Turkestan